Effectiveness of Tailored Reaction Time Training Drills in Addition to Warm-Up Sessions on Performance Parameters in Recreational Cricket Players - Tanishk Choksi1 , S Anandh2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: In the game of cricket, the players need very good reflexes to react to the situation. The players who plays very rarely (recreational players) end up with more injuries compared to elite players due to improper training session and warm-ups. The recreational players in over enthusiasm often end up with injury during the match. So to improve the performance of the recreational cricket players their reaction time should be improved. Thus recreational players need appropriate training and awareness of such therapeutic reaction time training drills like Ball Drop Drill, Reactive Gear Drill, Shuffle Reaction Ball Drill, Ball Catch Drill, Run Shuffle Drill, T-Drill, Multiple Slinger Drill and Mountain climber to Sprint along with regular warm up sessions are necessary for preventing injuries as well as improving the performance parameters of the cricket players. Objective: The objective of this study was to compare the effect of conventional and tailor made Reaction Time Training Drills sessions for recreational cricket players. Method: In this study, 26 individuals who played cricket for recreation (all male) were taken. They were equally divided into two groups i.e. Group A and Group B. Individuals in the age group of 19-30 years were included in this study, out of which 13(50%) players were in group A and 13(50%) were in group This consisted of those who played recreational cricket and did not have any training or experience in professional Cricket. Pre intervention and post intervention reaction time testing were taken. Group A received conventional training while Group B received Reaction Time Training Drill. Result: There was a significant effect of reaction time training on individuals of group B compared to conventional training in group A (p <0.0001). Conclusion: The tailored Reaction Time Training Drills are effective in improving performance and preventing injuries in recreational cricket players.